2024
DOI: 10.1101/2024.01.04.574135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age differences in functional connectivity track dedifferentiation of category representations

Claire Pauley,
Dagmar Zeithamova,
Myriam C. Sander

Abstract: With advancing age, the distinctiveness of neural representations of information declines. While the finding of this so-called "age-related neural dedifferentiation" in category-selective neural regions is well-described, the contribution of age-related changes in network organization to dedifferentiation is unknown. Here, we asked whether age differences in a) functional connectivity to category-selective neural regions and b) segregation of the visual network (i.e., network dedifferentiation) contribute to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Moreover, while age-related decreases in the specificity of brain function have been reported across various metrics (e.g., univariate and multivariate patterns of regional activity, interregional functional connectivity), it remains to be elucidated whether shared or distinct mechanisms underpin age-related differences across these measures. Emerging evidence indicates correlations across representational and network levels of neural specificity (Cassady et al, 2020;Pauley et al, 2024), suggesting at least partly overlapping mechanisms, as predicted by neuromodulatory accounts (Li et al, 2001;Li & Sikström, 2002). Indeed, a recent study also demonstrated administration of the dopamine precursor L-DOPA to enhance neural representations underlying spatial navigation in young and older adults (Koch et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, while age-related decreases in the specificity of brain function have been reported across various metrics (e.g., univariate and multivariate patterns of regional activity, interregional functional connectivity), it remains to be elucidated whether shared or distinct mechanisms underpin age-related differences across these measures. Emerging evidence indicates correlations across representational and network levels of neural specificity (Cassady et al, 2020;Pauley et al, 2024), suggesting at least partly overlapping mechanisms, as predicted by neuromodulatory accounts (Li et al, 2001;Li & Sikström, 2002). Indeed, a recent study also demonstrated administration of the dopamine precursor L-DOPA to enhance neural representations underlying spatial navigation in young and older adults (Koch et al, 2022).…”
Section: Discussionmentioning
confidence: 93%